The effect of Nb doping on ferroelectric properties of PZT thin films prepared from polymeric precursors - Souza, ECF; Simoes, A. Z.; Cilense, M.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2004)
Pure and Nb doped PbZr0.4Ti0.603 thin films was prepared by the polymeric precursor method and deposited by spin coating on Pt/Ti/SiO2/Si (100) substrates and annealed at 700 degreesC. The films are oriented in (1 1 0) and (1 0 0) direction. The electric properties of PZT thin films show strong dependence of the crystallographic orientation. The P-E hysteresis loops for the thin film with composition PbZr0.39Ti0.6Nb0.103 showed good saturation, with values for coercive field (E-c) equal to 60 KV cm(-1) and for remanent polarization (P-r) equal to 20 muC cm(-2). The measured dielectric constant (epsilon) is 1084 for this film. These results show good potential for application in FERAM. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: PZT; Nb doped PZT; FERAM; polymeric precursor